Effect of GA3 and row ratio of restorer (R) and CMS lines (A) on different characters and seed production of BRRI Hybrid Dhan2 (Bangladesh Journal of Agricultural Research, 2013)
An experiment was conducted at the experimental farm of Bangladesh Rice Research Institute (BRRI), Gazipur, during November to May 2009-10 to study the effect of GA3and row ratio of restorer and CMS lines on different characters and F1 seed production of BRRI hybrid dhan2. The treatments were of four levels of GA3 viz., (i) control, (ii) 150 g/ha, (iii) 250 g/ha, and (iv) 350 g/ha and five row ratios (R:A) viz., (i) 2:8, (ii) 2:10, (iii) 2:12, (iv) 2:14, and (v) 2:16. Different doses of GA3 ignificantly influenced growth and yield components of rice except total tillers/hill and 1000-grain weight. The highest F1 seed yield (2.34 t/ha) of BRRI hybrid dhan2 was obtained with an application of GA3 @ 250 g/ha which enhanced the maximum number of effective tillers, the highest number of grains/panicle, panicle exsertion rate and outcrossing rate. The lowest seed yield (1.10 t/ha) was produced without application of GA3 i.e., control. The row ratio of 2:12 and 2:8 produced the highest (2.05 t/ha) and the lowest (1.63 t/ha) F1seed yield, respectively. The interaction between GA3 and row ratio of restorer and CMS lines was significant for F1 seed yield. The highest F1 seed yield (2.90 t/ha) was obtained with the application of GA3 @ 250 g/ha at the row ratio of 2:12 (R: A). The lowest seed yield (0.95 t/ha) was recorded without application of GA3 (control) at row ratios of 2:16. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14391 Bangladesh J. Agril. Res. 37(4): 665-676, December 2012